2015
DOI: 10.1103/physrevx.5.041053
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Dissociative Ionization Dynamics of Molecular Nitrogen with Attosecond Time Resolution

Abstract: Studying the interaction of molecular nitrogen with extreme ultraviolet (XUV) radiation is of prime importance to understand radiation-induced processes occurring in Earth’s upper atmosphere. In particular, photoinduced dissociation dynamics involving excited states of N2+ leads to N and N+ atomic species that are relevant in atmospheric photochemical processes. However, tracking the relaxation dynamics of highly excited states of N2+ is difficult to achieve, and its theoretical modeling is notoriously complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 41 publications
(49 reference statements)
4
44
0
1
Order By: Relevance
“…[50][51][52][53] From the experiments of femtosecond laser-induced oxidation of CO on Ru(100), the CO oxidation driven by an electronic excitation (fast response) and the CO desorption coupled with phonons (slow response) were distinguished. 50 Also, the two-step mechanism of the CO desorption on Ru(0001) has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…[50][51][52][53] From the experiments of femtosecond laser-induced oxidation of CO on Ru(100), the CO oxidation driven by an electronic excitation (fast response) and the CO desorption coupled with phonons (slow response) were distinguished. 50 Also, the two-step mechanism of the CO desorption on Ru(0001) has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed how femtosecond VUV and XUV radiation can be used to reveal transient nuclear and electron dynamics in diatomic molecules [8][9][10][11][12] as well as in more complex molecular systems [13,14]. To probe such dynamics, the majority of the pump-probe-style experiments accomplished to date utilize not only pairs of XUV-IR pulses [8,[15][16][17][18], but also a combination of VUV-XUV pulses [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, it is described as the manipulation of 38 the electron-wave-packet dynamics of the unoccupied and 39 occupied electronic states of the material [4]. 40 For atomic and molecular gases such as argon [5], neon 41 [6], helium [7,8], N 2 [9], Br 2 [10], and hydrocarbons [11], probe [3,[12][13][14] were the subject of fewer studies. Besides 47 the change in absorption, Stark shift in He [15] and Ar [5], 48 Rabi oscillations [16] in Ne, line broadening [5], and quantum 49 beats [17,18] were recognized in the recorded XUV or photo-50 electron spectra.…”
Section: Introductionmentioning
confidence: 99%